KEMAMPUAN MENULIS IKLAN PADA SISWA KELAS VIII SMP NEGERI 5 KENDARI - Salwiana Udin; Fahruddin Hanafi; Aris Badara (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to describe the ability to write advertisements in class VIII students of SMP Negeri 5 Kendari. This study is classified as field research, which is carried out directly at SMP Negeri 5 Kendari as the object of research to collect data in accordance with the problems in this study. The population in this study were all class VIII students of SMP Negeri 5 Kendari with a total of 372 students consisting of 11 classes. The sample in this study was 158 with a 10% error rate. The sampling technique used was Proportionate Stratified Random Sampling, which is sampling by sorting student learning achievement from the highest to the lowest based on daily test scores. The data collection technique used in this study was by giving an advertisement writing test. The results showed data from 158 respondents, there were 50 respondents (31.64%) included in the category of being able to write advertisements and there were 108 respondents (68.35%) included in the category of not being able to write advertisements. Classically, it can be classified that the ability to write advertisements of class VIII students of SMP Negeri 5 Kendari is included in the category of not yet capable because it reaches 31.64% and has not exceeded the classical achievement criteria set, namely 85%.